ANALISIS CORPORATE GOVERNANCE DAN RASIO KEUANGAN DALAM MEMPREDIKSI KESULITAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR DI BEI - EKA SULITYO NINGSIH, SANI (Berkala Ilmiah Mahasiswa Akuntansi)
Financial distress is important information for various stakeholders to ensure the company will remain a going concern, or even otherwise would go bankrupt. Information about the financial distress will be able to help corporate managers to quickly determine the right strategy for his company. Therefore, this study aims to analyze the corporate governance and financial ratios to predict financial distress in companies manufacturing in Indonesia Stock Exchange 2006-2010 period. This study uses a case study design with one dependent variable, namely the hypothesis of financial distress, while the independent variable is corporate governance (the variable used is the agency cost and institutional ownership), and financial ratios (with the variables used are profitability ratios, liquidity ratios, the ratio solvency, and the ratio of market size). Study sample of 57 companies selected by purposive sampling technique. Techniques of data analysis using logit regression. The results show that corporate governance is represented by the agency cost and ownership of institutional and financial ratios are represented by the ratio of profitability, liquidity ratio, solvency ratio and the ratio of the size of the market is able to predict the onset of financial distress, so as to provide useful information and helps managers and other stakeholders for decision making.